If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/3(6x-5)-x=1/3-2(x-1
We move all terms to the left:
1/3(6x-5)-x-(1/3-2(x-1)=0
Domain of the equation: 3(6x-5)!=0
x∈R
Domain of the equation: 3-2(x-1)!=0We add all the numbers together, and all the variables
We move all terms containing x to the left, all other terms to the right
-2(x-1)!=-3
x∈R
-1x+1/3(6x-5)-(1/3-2(x-1)=0
We calculate fractions
-1x+(-2x+5)/(52x-43)+(-3x6/(52x-43)=0
We calculate terms in parentheses: +(-3x6/(52x-43), so:
-3x6/(52x-43
We multiply all the terms by the denominator
-3x6
We add all the numbers together, and all the variables
-3x^6
We do not support expression: x^6
See similar equations:
| -14j+15=5-3-13j | | 8+x-2=2+3x | | -3=4y+1 | | .2+2m=2.2 | | -10+19c+15=20+18c | | -16=30x | | 3x-19=42 | | 4+-c=-12 | | 3x+22=5x-7 | | -5(2-z)=10 | | -(a-2)=-14 | | 6x+24-8x=10 | | 3(2w-12)=24w | | 5(x+6)+10=60 | | (3x+5)(3x+5)=(x+1)(x+1) | | 4+-c=12 | | 5+x=-24 | | 34=8x-30 | | 2p-2-5p=10 | | 16.02=3g+3.63 | | 11y-4-2y=59 | | 11x+77=30x-40-6x | | -6y+12=2(y-2) | | 5x–3=2–(3x–3) | | 8x-20/12=2x-7 | | 2x-4(x-2)=-4+3x-3 | | (-1/5)n+7=2 | | -4x+7+5x=15 | | 2(v+6)=-4v+18 | | 2x^2-2x+33=0 | | 6b+7=-14 | | 10y=3y+56 |